OP06 Gut–brain axis revisited: Shedding light on the mucosa-associated microbial composition in IBD patients with psychological distress, anxiety, and depression. (25th January 2019) - Humbel, F; Juillerat, P; Scharl, M; Misselwitz, B; Schreiner, P; Macpherson, A; Rogler, G; von Känel, R; Yilmaz, B; Biedermann, L
Abstract: Background: The diversity and compositional stability of the gut microbiota over time has repetitively shown to be reduced in patients with IBD. Furthermore, distinctive alterations in microbial composition are not only considered a key pathogenic factor promoting intestinal inflammation, but might also affect the gut–brain axis, thereby ultimately impacting psychological well-being. In IBD patients, depressive symptoms and anxiety are frequent co-morbidities. Therefore, we aimed to elucidate a potential interplay between microbial composition and validated psychological outcome measurements in Swiss IBD patients. Methods: Study participants were 171 patients with available microbial sampling of the Swiss Inflammatory Bowel Disease Cohort Study (SIBDCS) who were in clinical remission (to exclude a potential impact of disease activity). All patients completed the Hospitality Anxiety and Depression Scale (HADS), the Perceived Stress Questionnaire (PSQ), the 36-item Short Form Health Survey (SF-36) and the Inflammatory Bowel Disease Questionnaire (IBDQ). Mucosa-associated intestinal microbiota composition from intestinal biopsies were sequenced via 16S rRNA high-throughput sequencing. Results: Regarding α diversity, we found significantly lower diversity in patients with higher perceived stress and no substantial differences in patients with high vs. low levels of anxiety and depressive symptoms, respectively. Beta diversity was significantly different in IBD patients with vs. without depression or anxiety (Figure 1). Principal component analysis of microbial β diversity according to severity (1 = moderately increased, 2 = severe vs. normal anxiety and depression) of psychological alteration (no UC patients with severe depression in our sample). Looking at specific OTUs, we found several alterations across groups (overview in Figure 2), Significant results of the quantitative abundance of specific microbes in correlation with extent of psychological distress (– indicating a negative correlation; q -values: corrected; p value, according to Benjamini and Hochberg false discovery rate). Including, for instance, significant increases in represents of Proteobacteria, such as Desulfovibrio ( p = 0.001) in UC and decreases in numerous genus of Firmicutes, such Lachnospiraceae ( p < 0.001) in CD and UC patients with depression or decreases in Lactobacillales (Streptopcoccaceae) in CD patients with anxiety ( p < 0.001). Conclusions: We found significant alterations in the intestinal mucosa-associated microbiome composition in IBD patients in remission in relation to psychological well-being and quality of life. Further studies are warranted to gain more insight into the direction of this link and to investigate whether intestinal inflammation subsequent to microbial alterations or microbial metabolites itself may impair psychological well-being.